(untitled) (Boston, 2004)
This anthology is based on a distinct theoretical framework that provides coherence and cohesion to the readings included, presenting the phenomena of racism, sexism, heterosexism, and classism as interlocking systems of oppression. Resting upon this oppression model are two sets of theories, one concerned with the phenomenon of privilege--the companion of oppression--and the other with resistance--the response to oppression
Keywords: Social stratification,Oppression (Psychology),Stereotypes (Social psychology),Racism,Sexism,Social ethics,Phân tầng xã hội,Sự áp bức (Tâm lý),Định kiến (tâm lý xã hội),Phân biệt chủng tộc,Phân biệt giới tính